Of mice and women: Pat Barker’s retelling of the “Iliad” - Curyłło-Klag, Izabela (Litteraria Copernicana, 2020)
The article discusses Pat Barker’s latest novel, The Silence of the Girls (2018), which follows the events of the Iliad from the perspective of Briseis and other women abducted and reduced to sex-slaves during the Trojan conflict. The main focus of the analysis are the ways in which Barker challenges the ellipses of the Homeric original. By freeing the silenced voices of unwilling and powerless participants in the epic events, she deconstructs one of the key myths of the Western civilization, exposing its inglorious, misogynistic underpinnings. Additionally, what comes under scrutiny is Barker’s exploration of the immediacy of sensory experience as she describes the viscera of war, as well as the messy realities of life in a rat-infested army camp. Artykuł omawia najnowszą powieść Pat Barker, The Silence of the Girls (2018), która stanowi przepisanie wydarzeń Iliady z perspektywy Bryzejdy i innych kobiet wziętych w niewolę i sprowadzonych do roli nałożnic w trakcie wojny trojańskiej. Głównym celem analizy jest prześledzenie sposobów, w jaki Barker rozprawia się z przemilczeniami homeryckiej opowieści. Uwalniając stłumione głosy bezsilnych kobiet, wplątanych wbrew woli w przedstawione w eposie konflikty, pisarka dekonstruuje jeden z kluczowych mitów zachodniej cywilizacji, odsłaniając jego niechlubne, mizoginiczne podstawy. Ponadto artykuł zwraca uwagę na wyeksponowanie bezpośredniości doznań zmysłowych podczas opisów okropności wojny, a także w obrazach życia w obozowisku wojskowym dotkniętym przez plagę szczurów.